2010
DOI: 10.3855/jidc.1153
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of bacterial vaginosis in cases of abnormal vaginal discharge: comparison of clinical and microbiological criteria

Abstract: Introduction: Bacterial vaginosis is a polymicrobial syndrome involving replacement of normal vaginal hydrogen peroxide producing lactobacilli by a variety of mycoplasmas and Gram-negative rods. Bacterial vaginosis has been conventionally diagnosed using Amsel criteria (a clinical method) or Nugent's score (a laboratory method with higher reproducibility). This study was undertaken to compare the diagnostic ability of the Amsel criteria with that of Nugent's score among patients presenting with abnormal vagina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
1
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 22 publications
8
27
1
13
Order By: Relevance
“…This could indicate that production of odor is a cooperative process depending on the particular microbiota composition. Indeed, odor is not universally detected in women who are BV-positive by Nugent score [40], and previous studies suggest that particular taxa are more associated with odor [3,41]. Symbiotic relationships may be common in the vaginal environment, as another has been described where G. vaginalis produces amino acids that promote the growth of Prevotella bivia [42].…”
Section: Resultsmentioning
confidence: 99%
“…This could indicate that production of odor is a cooperative process depending on the particular microbiota composition. Indeed, odor is not universally detected in women who are BV-positive by Nugent score [40], and previous studies suggest that particular taxa are more associated with odor [3,41]. Symbiotic relationships may be common in the vaginal environment, as another has been described where G. vaginalis produces amino acids that promote the growth of Prevotella bivia [42].…”
Section: Resultsmentioning
confidence: 99%
“…Another investigator from Kolkata, India, has reported that the presence of clue cells correlates best with a positive diagnosis by Nugent's score [1]. This result indicates that by adding a score for the presence/absence of clue cells to each of these 2 methods, one can enhance the diagnosis of BV, which can be superior to the methods of Nugent et al and Hay et al…”
Section: Discussionmentioning
confidence: 97%
“…Accurate diagnosis of BV is somewhat challenging. In addition to scientific considerations, choosing a method for its diagnosis requires consideration of complexity, cost, and the frequency of un-interpretable specimens [1]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial vaginosis does not evolve from a commonly defined bacterial infection caused by one agent, but is a disorder of the vaginal microbiome. Therefore, the appropriate diagnosis of BV is demanding and the decision about the method of choice for its diagnosis requires a review of complexity, cost, and the constancy of samples difficult to interpret [18].…”
Section: Discussionmentioning
confidence: 99%